Irregular migrants and informal institutions : how do their interactions with formal institutions affect policy effectiveness? - Low, Choon Chyuan (2017)
This paper aims to analyze the different types of informal institutions in Malaysia and how they contributed to the survival of irregular migrant workers. By studying the interactions between formal and informal institutions, we are able to learn how Malaysia’s immigration policy effectiveness is being affected by informal institutions. The typology invented by Helmke and Levitsky had identified four types of interactions between formal and informal institutions: complementary, accommodating, substitutive and competing interactions. By using the typology to guide this research, I interviewed irregular migrants, agents, employers and non-governmental organizations and conducted ethnographic observations in several migrant communities in Kuala Lumpur, Malaysia. Through the interviews and observations, I found that some informal institutions enhanced immigration policy effectiveness; some informal institutions substitute for the policy gaps left by the formal institutions; some violate the policy objectives without violating laws and some challenge the state’s capacity to govern the society. This paper provides several policy recommendations on interactions with different informal institutions.